Los ingresos corrientes y la descentralización fiscal en el municipio de Tunja (2013)
This paper elaborates on the current income of the municipality of Tunja and impact regarding issues of decentralization and existing legal norms. Major tax reforms are identified, briefly discusses the areas of current revenues (tax, non-tax and transfers), and impact against variables such as audit, economic sectors, regional disparities and theories implemented even in some cases their entirety.